Optimism Bias Towards the Covid-19 Pandemic - Anita Englin Henukh; Indra Yohanes Kiling; M. K. P. Abdi Keraf (Universitas Nusa Cendana, 2022)
The COVID-19 pandemic has forced people to be isolated from various things related to activities outside the home, both work and acquaintances and even families. Can only interact with people who live under the same roof. This is done to avoid the cause of the coronavirus. This transition to limited interaction with others may have influenced people`s optimism bias. This study uses a qualitative method to describe the optimism bias of the people of Kupang City towards the COVID-19 pandemic. This research uses descriptive qualitative research with snowball data collection methods and interview sessions with 10 participants. This study shows that the people of Kupang City are indifferent or disobedient to government regulations, especially health protocols, because they consider COVID-19 only as a common disease, and they have an optimism bias even though they do not comply with health protocols, they are still healthy until now.